Pengelolaan Konflik Aktivitas Bisnis Perspektif Islam Pada Manajemen Pasar Induk Puspa Agro Jawa Timur - Indraswari, Citra Rahayu; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Conflict is something that can not be separated in the process of management of the company. Conflict that managed well will be able to make a positive contribution to the business activities and the achievement of corporate goals. This study used a qualitative research methodology with a case study approach. The selection of a qualitative methodology based on the problem formulation used in this studyThe results of this study indicate that the conflicts that happened in management Central Market Puspa Agro caused by internal and external factor. Internal factor is derived from obscurity powers, functions and roles, monitoring and evaluation weakness, slowness of responds to the problems, the competence of individual differences, the target and task interdependence. External factors consist of the presence of government policies and industry demands. The effect of conflicts are functional and dysfunctional. Conflicts levels are low, optimal and high.Conflict management is applied by stimulation, reduction of conflict and conflict resolution methods. Conflict stimulation methods include the application of the system of reward and punishment and the different treatment of habit . Conflict reduction methods include the provision of a forum for dialogue, joint activities and creating new challenges. Conflict resolution methods include the expansion of resources, compromise, change the variable structure of the company, avoiding and otorative command.